How trust functions in the context of identity work. (June 2015) - Driver, Michaela
The study develops a new perspective on trust in organizations by exploring trust in the context of identity work. An analysis of stories in which employees describe how they experienced when the employer violated their trust suggests that individuals draw on trust discourse to validate who they are. Using a psychoanalytically informed framework, the study examines the complexities of trust in the context of struggles with the conscious self and unconscious desire. Trust emerges as a placeholder for what is really wanted but impossible to attain. Based on this perspective, the study offers new insights on why individuals trust, why trust may be resilient, why trust may be engineered and how trust mirrors identity as an elusive and fleeting accomplishment.